Unified generator system - Basyuk, O. P. (Technology and design in electronic equipment, 2025)
Suggested in the article is a brand new concept of the synchronization of control frequencies of the transmitting and receiving devices. In the case of its implementation a significant increase can be achieved in the efficiency of the new (upgraded) information systems while significantly reducing their cost. The presented considerations may be regarded merely as an idea, which being positively assessed will require the development of optimal ways to implement the system as a whole, its individual components and methods of implementation.